Comparative Analysis of Nextcloud and Owncloud Performance as Infrastructure as a Service (IaaS) Based Cloud Storage - Haryani, Prita; Ariyana, Renna Yanwastika; Majid, Iqbal Abdul; Susanto, Fx. Guntur Putra (Institut Teknologi Dirgantara Adisutjipto, 2024)
Physical data storage using flash drives or local computer storage continues to be used for document archiving in database laboratories. Archived documents include laboratory inventory modules, practical course modules, practitioners' attendance cards, and students' task and response files. Utilizing cloud storage has emerged as a solution to these issues, enabling data to be easily accessed from anywhere via an internet connection. Numerous cloud storage applications now feature advanced functionalities; however, each cloud storage company varies regarding access speed, storage capacity, security, and costs. This study aims to analyze the performance of two cloud storage applications, Nextcloud and Owncloud, using throughput as a parameter. Test results demonstrated that Nextcloud's performance in file upload throughput was higher at 1065 bps compared to Owncloud's 850 bps. Similarly, in file download throughput, Nextcloud exceeded Owncloud's throughput of 2960 bps against 2564 bps. These results indicate that Nextcloud's performance surpasses Owncloud's in both file upload and download operations